Tristeza do Jeca: diálogo, consciência e libertação: uma análise sob a ótica da educação popular (1950 a 1961) - Paula, Juscimar Maria de (2014)
This research aims to identify the conception of education in the movie Tristeza do Jeca , as well as its relevance to the history of education in Brazil. The time frame of the research is anchored in the period 1950-1961, a period that goes from the character\'s first appearance on screen Jeca until the release of the film in question . The relevance of the study is guided by the reflection of existing elements in this work as satyrs propagator feature key factors for building a period of Brazil\'s history process. To do so , the problematic part of the following questions : What is Cinema ? Is the Brazilian (political economic, social and cultural) context presented in this work? How does this film contributes to the understanding of the Brazilian educational culture in the 1950s and 1960s? What is the concept of education that permeates? How is represented the conflict between urban and rural cultural practices within the defined period? It is, thus, a qualitative research, documentary stamp, based on the query and analysis filmography Mazzaropi. The paper is organized into three chapters. Initially, we situate the contribution of the film \'s Sadness Jeca for the History of Education, specifically the education that is independent of formal learning institutions. Then, if contextualized historical conditions, political, economic, social and cultural rights in Brazil in the 1950s and 1960s, drawing a parallel between this historical period and Jeca , central character of this film. Furthermore, we discussed the thought of Paulo Freire, in order to defend the idea that our object is an instrument of popular education. Still in this chapter we analyze the educational legislation and the quantitative and qualitative aspects of Brazilian education in bounded time frame for us. Issues related to the analysis of the film Sadness of Jeca and the freireanas categories and the popular education in the perspective of this work were depeloped in the last section. As a result, it was found that the film Sadnessof Jeca is a mechanism for popular education, it publishes political and socio-cultural practices of their public education, with the development of critical- reflective consciousness. When viewing the socioeconomic context of the development of capitalist practices and social injustices that made up the Brazilian society in the decades since bounded, show a political base that encourages dialogue instead of silence that a large part of the Brazilian people was submitted, stressing that freedom is an achievement that men and women who are able to resist and defend its values and ideals.